Virtual Reality Relaxation for Patients With a Psychiatric Disorder: Crossover Randomized Controlled Trial - Veling, Wim; Lestestuiver, Bart; Jongma, Marieke; Hoenders, H J Rogier; van Driel, Catheleine (JMIR Publications, 2021)
BackgroundVirtual reality (VR) relaxation is a promising mental health intervention that may be an effective tool for stress reduction but has hardly been tested in clinical trials with psychiatric patients. We developed an easy-to-use VR self-management relaxation tool (VRelax) with immersive 360° nature videos and interactive animated elements. ObjectiveTo investigate the immediate effects of VR relaxation on negative and positive affective states and short-term effects on perceived stress and symptoms in patients with a psychiatric disorder, compared to standard relaxation exercises. MethodsA randomized crossover trial was conducted in 50 patients receiving ambulatory treatment for anxiety, psychotic, depressive, or bipolar disorder. Participants were randomly assigned to start with VRelax or standard relaxation and used both interventions for 10 days at home. They completed 8 visual analog scales of momentary negative and positive affective states before and after each session. Global perceived stress and psychiatric symptoms were measured before and after both intervention periods. Treatment effects were analyzed with multilevel mixed model regression analyses and 2-way analysis of variance. ResultsBoth VRelax and standard relaxation exercises led to a statistically significant immediate improvement of all negative and positive affective states. Compared to standard relaxation, VRelax resulted in a significantly greater reduction of total negative affective state (change 16.2% versus 21.2%; t1684=−2.02, 95% CI −18.70 to −0.28; P=.04). Specifically, VRelax had a stronger beneficial effect on momentary anxiety (t1684=−3.24, 95% CI −6.86 to −1.69), sadness (t1684=−2.32, 95% CI −6.51 to −0.55), and cheerfulness (t1684=2.35, 95% CI 0.51 to 5.75). There were no significant differences between short-term effects of the two treatments on global perceived stress and symptoms. ConclusionsIf the results of this trial are replicated and extended, VRelax may provide a much-needed, effective, easy-to-use self-management relaxation intervention to enhance psychiatric treatments. Trial RegistrationNetherlands Trial Register NTR7294; https://www.trialregister.nl/trial/7096